Analisis Kuat Tekan Beton Ringan Dengan Subtitusi Material Kertas Koran Dan Fly Ash - vike itteridi; edowinsyah (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2019)
Development in the field of construction in the modern era shows a very rapid development, including in the construction of housing, offices, hospitals and so on. Concrete as a construction material has long been used and widely applied by the community because it has advantages easily formed according to construction needs. The development of concrete technology has also continued to develop with the presence of high-strength concrete. The process of making lightweight concrete certainly requires mixed materials that have low specific gravity. One alternative material that can be used is newsprint and fly ash, both materials are materials that have a low specific gravity and are easy to work on, the addition of fly ash and newsprint so that the relationship of compressive strength and weight of concrete influence each other, the more addition of fly ash and newsprint, the compressive strength increases and the weight of the concrete increases.